Contribución al estudio histológico de los islotes de Langerhans en los anfibios - Prieto Díaz, Herberto Elías (1941)
During summer, in Bufo arenaum’s (Hensel) pancreas, endocri- nic elements are expressed by typical and atypical small islands and by solitary Cells. The apparition of the two last elements is observed by “acinous” Cells transformation. Typical and atypical small islands are constituted by A. and B. cells. There are (also ‘‘argyrophiles” cells. Solitary elements are of A. type. Apparition of insular elements by “ductal” epithelium is rarely observed. Capillaries of the small islands are of “sinusoid” type.